Reviews : A relative revolution. (14th October 2019) - Robinson, Andrew
Abstract: It is difficult to imagine the modern world without the life and work of Albert Einstein. There exist some 1750 books about him. In this review I look at four that have been recently published: No Shadow of a Doubt by Daneil Kennefick; Einstein's War by Matthew Stanley; Proving Einstein Right by S James Gates Jr and Cathie Pelletier; and Einstein's Wife by Allen Esterson and David C Cassidy with contribution by Ruth Lewin Sime.